2014
DOI: 10.1190/tle33020182.1
|View full text |Cite
|
Sign up to set email alerts
|

Insights into sweep efficiency using 4D seismic at Halfdan field in the North Sea

Abstract: A repeat 4D seismic survey was acquired in 2012 over the Halfdan oil field in the Danish North Sea Central Graben. The main objectives were to understand the lateral and vertical waterflood sweep in the reservoir, to identify unswept areas, to guide future well interventions, and to improve the reservoir model. The main oil reservoir is the Cretaceous chalk Tor Formation, and the field is developed via a line-drive waterflood. The reservoir saturation changes caused by water injection lead to large changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…The last example is based on the configuration of a layered hydrocarbon field in the North Sea [53,54]. The reservoir is exploited by several long (2-5 kilometer) parallel horizontal wells.…”
Section: North Sea Field Examplementioning
confidence: 99%
“…The last example is based on the configuration of a layered hydrocarbon field in the North Sea [53,54]. The reservoir is exploited by several long (2-5 kilometer) parallel horizontal wells.…”
Section: North Sea Field Examplementioning
confidence: 99%
“…Many of the Danish gas fields in the North Sea are produced by natural depletion with gas/fluid expulsion and related compaction as drivers (Hatchell et al 2007;Danish Energy Agency 2013;Calvert et al 2014;Schutjens et al 2019). Often, reservoir compaction is translated into seabed subsidence, which has a direct adverse effect on production facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the Dan field was produced by natural depletion -with water injection initiated only after several years of production. Analysis of timeshift data from the 4D seismic surveys acquired in the Halfdan/Dan field in 2005 and 2012 (Calvert et al 2014; indicated that waterflooding might have slowed down reservoir compaction in the area. Nonetheless, albeit reduced, seabed subsidence has continued -suggesting that the compaction drive remained active.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Upper Maastrichtian, the average porosity can have values of 25-30%, whereas a sharp decrease in porosity to about 10-15% is observed in the Lower Maastrichtian to Campanian layers (Albrechtsen at el., 2001). Data from 4D seismic survey and reservoir modelling in conjunction with the production and geologic data suggest that there might be unswept areas in the deep reservoir layers (Calvert et al, 2014). RJD technique is considered as a potential method for accessing the unswept areas and improving oil recovery.…”
Section: Introductionmentioning
confidence: 99%